Many Faces of Adrenal Lesions in a Large Patient Cohort: What Has Changed Over the Last Two Decades? - Saydam, Basak Ozgen; Baris, Mustafa; Adiyaman, Suleyman Cem; Demir, Tevfik; Kocdor, Mehmet Ali; Demir, Omer; Secil, Mustafa; Yener, Serkan (Experimental and Clinical Endocrinology & Diabetes, 2023)
Objective To review the presentation characteristics, clinical and hormonal evaluations, and histopathological results of patients with adrenal lesions over a 21-year period and evaluate the changes across the two decades.Methods This single-center, retrospective study included 1003 patients with adrenal lesions who presented to our department between 2000 and 2021. Clinical, metabolic, hormonal, radiological, and pathological data of the patients were collected.Results Forty-seven percent of the lesions were non-functioning adrenal adenomas. Possible autonomous and autonomous cortisol secretion were detected in 22.2% of the patients. The percentages of the patients diagnosed with pheochromocytoma, primary hyperaldosteronism, adrenal Cushing syndrome, adrenocortical carcinoma, and adrenal metastasis were 7.4%, 4.8%, 4.7%, 0.9%, and 5.6%, respectively. Adrenalectomy was performed in 31.3% of the patients. Functional adrenal lesions were the leading cause of surgery (46.5%), followed by large size and/or suspicious imaging features (38.6%). Among the patients referred to surgery due to large size (≥6 cm), the diagnosis in 19% was metastasis, and in 12.1%, it was primary adrenocortical carcinoma. In patients with adrenal lesions with a size of 4–6 cm and suspicious imaging properties, the rates of metastasis and primary adrenocortical carcinoma were 44.4% and 4.8%, respectively. From the first to the second decade, major differences in presentation characteristics were increased detection of bilateral lesions and increased prevalence of possible autonomous and autonomous cortisol secretion.Conclusions Adrenal lesions are common in the adult population, and while it is important to avoid overtreatment, hormone secretion, and malignancy should not be overlooked.
Keywords: adrenal incidentaloma; adrenal lesions; adrenocortical carcinoma; subclinical Cushing syndrome; autonomous cortisol secretion